Insight Into the Diversity and Possible Role of Plasmids in the Adaptation of Psychrotolerant and Metalotolerant Arthrobacter spp. to Extreme Antarctic Environments - Romaniuk, Krzysztof; Golec, Piotr; Dziewit, Lukasz (Frontiers in Microbiology, 2018)
Arthrobacter spp. are coryneform gram-positive aerobic bacteria, belonging to the class Actinobacteria. Representatives of this genus have mainly been isolated from soil, mud, sludge or sewage, and are usually mesophiles. In recent years, the presence of Arthrobacter spp. was also confirmed in various extreme, including permanently cold, environments. In this study, 36 psychrotolerant and metalotolerant Arthrobacter strains isolated from petroleum-contaminated soil from the King George Island (Antarctica), were screened for the presence of plasmids. The identified replicons were thoroughly characterized in order to assess their diversity and role in the adaptation of Arthrobacter spp. to harsh Antarctic conditions. The screening process identified 11 different plasmids, ranging in size from 8.4 to 90.6 kb. A thorough genomic analysis of these replicons detected the presence of numerous genes encoding proteins that potentially perform roles in adaptive processes such as (i) protection against ultraviolet (UV) radiation, (ii) resistance to heavy metals, (iii) transport and metabolism of organic compounds, (iv) sulfur metabolism, and (v) protection against exogenous DNA. Moreover, 10 of the plasmids carry genetic modules enabling conjugal transfer, which may facilitate their spread among bacteria in Antarctic soil. In addition, transposable elements were identified within the analyzed plasmids. Some of these elements carry passenger genes, which suggests that these replicons may be actively changing, and novel genetic modules of adaptive value could be acquired by transposition events. A comparative genomic analysis of plasmids identified in this study and other available Arthrobacter plasmids was performed. This showed only limited similarities between plasmids of Antarctic Arthrobacter strains and replicons of other, mostly mesophilic, isolates. This indicates that the plasmids identified in this study are novel and unique replicons. In addition, a thorough meta-analysis of 247 plasmids of psychrotolerant bacteria was performed, revealing the important role of these replicons in the adaptation of their hosts to extreme environments.